2009
DOI: 10.1073/pnas.0908855106
|View full text |Cite
|
Sign up to set email alerts
|

Neural responses to sanction threats in two-party economic exchange

Abstract: Sanctions are used ubiquitously to enforce obedience to social norms. However, recent field studies and laboratory experiments have demonstrated that cooperation is sometimes reduced when incentives meant to promote prosocial decisions are added to the environment. Although various explanations for this effect have been suggested, the neural foundations of the effect have not been fully explored. Using a modified trust game, we found that trustees reciprocate relatively less when facing sanction threats, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
86
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 59 publications
9
86
0
1
Order By: Relevance
“…Several studies have reported negative relationships between amygdala activity and economic trust (6)(7)(8), but other studies suggest no amygdala involvement in economic trust behaviors (6,9,10). A potential reason for this inconsistency is that in human research, the amygdala is typically investigated and discussed as a single unit (11,12).…”
mentioning
confidence: 99%
“…Several studies have reported negative relationships between amygdala activity and economic trust (6)(7)(8), but other studies suggest no amygdala involvement in economic trust behaviors (6,9,10). A potential reason for this inconsistency is that in human research, the amygdala is typically investigated and discussed as a single unit (11,12).…”
mentioning
confidence: 99%
“…Spitzer et al (2007) found that activations in the lateral orbitofrontal cortex (LOFC) and dlPFC were positively correlated with individuals' increase in norm compliance when punishment threat was present. In contrast, Li et al (2009) observed decreased activations in the LOFC and ventromedial PFC (vmPFC) when punishment threat was present.…”
Section: Introductionmentioning
confidence: 80%
“…Closer examination of previous studies reveals that those reporting a detrimental effect typically adopted intentional punishment threat imposed by the interacting partner on behalf of his/ her own interest (Fehr and Rockenbach, 2003;Li et al, 2009), whereas those reporting a facilitatory effect involved unintentional punishment threat, which was introduced by an impartial third-party (e.g., computer program) for the sake of fairness (Spitzer et al, 2007;Ruff et al, 2013). However, to our knowledge, no studies have investigated directly the role of intention behind punishment threat in norm enforcement.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations